2016
DOI: 10.1007/s11606-016-3733-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Problematic Substance Use in HIV Care: Which Questions Elicit Accurate Patient Disclosures?

Abstract: BACKGROUND: Substance use is associated with higher rates of antiretroviral non-adherence and poor HIV outcomes. This study examined how HIV care providers assess substance use, and which questions elicit accurate patient disclosures. METHODS: We conducted a conversation analysis of audio-recorded encounters between 56 providers and 162 patients living with HIV (PLWH) reporting active substance use in post-encounter interviews (cocaine or heroin use in the past 30 days, > 4 days intoxicated in past 30 days, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The number of alcohol users in this study was lower than that in previous studies because some HIV-infected Koreans, once aware of the fact that they had been infected, had stopped drinking alcohol and were actively seeking disease control [21]. However, only about half of the providers in an HIV clinic assessed problematic substance usage, including alcohol [22]. In the study by Othieno et al, screening for alcohol use was not routinely performed, and available protocols were not in place to manage alcohol-related disorders [23].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The number of alcohol users in this study was lower than that in previous studies because some HIV-infected Koreans, once aware of the fact that they had been infected, had stopped drinking alcohol and were actively seeking disease control [21]. However, only about half of the providers in an HIV clinic assessed problematic substance usage, including alcohol [22]. In the study by Othieno et al, screening for alcohol use was not routinely performed, and available protocols were not in place to manage alcohol-related disorders [23].…”
Section: Discussionmentioning
confidence: 61%
“…It is suggested that alcohol screening and treatment, a nonroutine practice in Korea, should be a first step in adherence improvement for people who drink and take antiretroviral drugs, particularly during a stable period of disease progression [24]. When assessing alcohol consumption, an open-ended or normalizing question that includes the phrase "last time," such as "When was the last time you used alcohol?," was proven effective in assessing the alcohol consumption of patients with HIV [22].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in another setting characterized by frequent physician-patient interaction (women receiving prenatal care), higher prevalence of cocaine and heroin use was estimated based on medical charts than on face-to-face interview (42). We did not directly explore characteristics of the patient-provider relationship that facilitated physician awareness of substance use; other studies have suggested that patient disclosure of substance use is more likely when physicians use broad or normalizing questions (43), when assessing illicit substance use versus alcohol abuse (41), and in the context of more-frequent provider visits (44). Our estimates of sensitivity and specificity of MRR and SI for detecting recent substance use may be transportable to other HIV clinics, given lack of evidence that sensitivity varied by patient demographics, but are not likely transportable to general practice settings.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants' perspectives and advice on creating patient comfort in clinic-based IPV assessment can translate to other sensitive topics such as palliative and end of life care and often-stigmatized areas like HIV or other sexually transmitted infection treatment. We suggest that emphasizing emotional comfort patient comfort can be a beneficial addition to the existing patient-centered and open-ended communication methods that are already commonly applied in these areas [82][83][84][85].…”
Section: Discussionmentioning
confidence: 99%